P077 What are the perspectives of key informants on the implementation hiv self-testing (HIVST) in england? a qualitative study of barriers, facilitators and anticipated impacts. (8th June 2017) - Witzel, TCharles; Burns, Fiona M; Weatherburn, Peter; Rodger, Alison J
Abstract : Introduction: HIVST is a new approach for individuals to test themselves for HIV in a location and at a time of their choosing using a rapid diagnostic test. This approach has the potential to increase testing uptake and frequency. Questions remain about where and how to situate HIVST in a landscape of diverse HIV testing provision. This study aims to understand the perspectives of key informants on the implementation of HIVST. Methods: In order to inform development an intervention for use in a trial recruiting men who have sex with men (MSM) and transgender people, we conducted in-depth interviews with 17 key informants (KIs) including clinical staff in HIV and STI services, voluntary sector service providers and HIV testing commissioners. Interviews were transcribed verbatim and analysed using a thematic framework analysis. Results: KIs valued HIVST for providing patients with additional choice. Careful attention to intervention design was important as local context and client group shaped anticipated patient response to HIVST. Interventions should deliver HIVST through integrated approaches that provide direct pathways into additional testing services and HIV care. Anticipated impacts were a loss of support from face-to-face testing services, the possibility of increased risk of self-harm, reduced STI detection, but conversely HIVST also increased potential for empowerment. Discussion: HIVST interventions should be responsive to context, taking into account both local and national needs. Concerns centred on potential negative impacts indicating that innovative service delivery designs which address these may be key to KI buy-in for HIVST implementation and patient outcomes.